Changes in Place Attachment Among Relocated Residents in Post-Disaster Housing Environments - Zahra Shobkolaie; Seyed-Abbas Yazdanfar; Saeid Norouzian-Maleki (علوم محیطی)
Introduction: Place attachment is the basis for understanding the complex nature of human relationships with the surrounding environment. Humans have evolved the basic need for social communication, in such a way that they must create and maintain interpersonal relationships and gain a sense of security, acceptance, and belonging from these relationships. Natural hazards are events such as earthquakes, typhoons, floods, and landslides, which have the potential to pose a significant threat to human health and safety, property, critical infrastructure, and homeland security. The increase in losses can be explained to a large extent by higher levels of human activity and the accumulation of economic assets in hazard-prone areas. The natural hazards cause physical damage to residential neighborhoods and give rise to psychological distress. There is a growing interest in place attachment as a coping strategy in response to natural hazards. Also, some studies have shown that there is a complicated relationship between place attachment and perceived risk. The concept of attachment is influenced by human aspects arising from the fields of psychology and sociology, and the other part arises from the field of architecture, which changes various events such as the relocation of residents after the disasters. In architecture, less attention has been paid to the physical aspect of people’s sense of attachment after disasters. Therefore, in this study, the concept of attachment to a place at the level of residential neighborhoods is measured based on three components: architecture, urban environment, and nature. The architectural component consists of sub-components of scale, density, privacy, furniture, legibility, view, and coherence. The urban component has the sub-components of urban services, access, hierarchy, furniture arrangement, diversity of activities, meeting needs and elements of the city. Finally, the natural landscape component has the sub-components of green space and climate comfort. Material and Methods: The method of this research is that after field harvest and typology compilation of the residential neighborhood of the province located in Neka city, a researcher-made questionnaire was made by random sampling method and by G-Power software with a sample size of 340 people in different valleys of distribution residents. Then, with the help of statistical analysis, the physical characteristics of the residential neighborhood as an independent variable and the characteristics of the concept of attachment as a dependent variable were evaluated. Results and Discussion: The findings revealed that there was a direct relationship between components of the urban environment (r=0.815), the natural landscape (r=0.768), the architecture (r=0.761), and the attachment of residents after disasters (P<0.05). The standardized regression coefficients (β) for the urban components, specifically activity diversity (β = 0.318, P < 0.001) and efficient layout (β = 0.317, P < 0.001), indicate significant associations. Also, the β value for the architecture components, including legibility, was 0.345 (P<0.001), and for the natural landscape component, including climatic comfort was 0.472 (P<0.001). Conclusion: The initial decisions of designers and planners in selecting effective physical variables combined with the design of spaces and other physical factors will lead to a change in the level of attachment of residents after disasters in Neka city.